2017
DOI: 10.3171/2015.12.jns151499
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative executive function in adult moyamoya disease: a preliminary study of its functional anatomy and behavioral correlates

Abstract: OBJECTIVE Chronic frontal hemodynamic disturbances are associated with executive dysfunction in adult patients with moyamoya disease (MMD). However, the impact of surgical revascularization on executive dysfunction and its underlying mechanism remains unclear. The aim of the present study was to examine the postoperative radiological correlates of cognitive improvement and thereby explore its underlying mechanism. METHODS Fourteen patients who met the inclusion criteria were identified at Huashan Hospital, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 29 publications
(38 reference statements)
2
32
0
Order By: Relevance
“…Anatomical location of advanced cognitive function has undergone intensive investigation. Despite a few studies reporting a correlation between hemodynamic compromise in temporal lobe and cognitive impairment (26,30), more researchers found that regions in the frontal lobe are linked to executive function, both from aspects of hemodynamics and metabolism (4,15,31,32). Using multivariate linear regression to adjust for confounders, we found that the average CBF of the left temporal lobe independently associated with processing speed.…”
Section: Discussionmentioning
confidence: 66%
“…Anatomical location of advanced cognitive function has undergone intensive investigation. Despite a few studies reporting a correlation between hemodynamic compromise in temporal lobe and cognitive impairment (26,30), more researchers found that regions in the frontal lobe are linked to executive function, both from aspects of hemodynamics and metabolism (4,15,31,32). Using multivariate linear regression to adjust for confounders, we found that the average CBF of the left temporal lobe independently associated with processing speed.…”
Section: Discussionmentioning
confidence: 66%
“…Cognitive dysfunction resulting from MMD has begun to garner the attention of researchers studying the disorder [ 14 , 15 , 18 ]. However, despite the increasing use of rs-fMRI to investigate brain function in other cognitive disorders, few published studies have used rs-fMRI to investigate cognitive dysfunction in MMD, [ 17 , 20 , 23 ]. In this study, we conducted rs-fMRI in a group of patients with MMD who had minimal ischemic lesions and no prior history of revascularization surgery, because such patients require early detection of ischemic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Such research has revealed several patterns of brain function associated with MMD. For example, the averaged square root of power maps of low-frequency BOLD signals was found to identify disease-related changes in patients with MMD and predict postsurgical cognitive improvement [ 17 , 20 ]. Furthermore, attenuated local synchronization of low-frequency BOLD signals has been associated with worse cognitive performance in patients with MMD [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations